Professional Judgment: Thinking, not Just Calculating - RAZUMOVAK. М. (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2024)
The article reveals the essence of professional judgment as a key element in the field of audit, accounting and related activities, which ensures flexible, informed decision-making in complex or non-standard situations. It is argued that professional judgment needs to be employed by specialists in adapting international standards to the national context, assessing risks, determining materiality and choosing appropriate verification methods, collecting and evaluating audit evidence, and forming an opinion on financial reporting. The study demonstrates that without professional judgment it is impossible to ensure the quality of the audit, the reliability of financial reporting and compliance with regulatory requirements. This is not only technical competence, but also a manifestation of ethics, experience, and responsibility that builds trust in the accounting and auditing profession.It is argued that professional judgment is critically important due to its being a bridge between standards and reality. In complex or non-standard situations, no regulation provides a ready-made answer. The judgment allows the auditor, accountant or another specialist to choose a reasoned decision taking into account the risks, context, economic essence of operations and expectations of reporting users. It ensures flexibility without loss of responsibility, adaptation of international norms to national practice, trust in the professional community, quality, ethics and relevance of generated reports and professional decisions.